A Retrospective Cohort Analysis of Pharmacologic VTE Prophylaxis and Padua Prediction Score in Hospitalized Patients With Chronic Liver Disease. (February 2017) - Moorehead, Kaitlyn J.; Jeffres, Meghan N.; Mueller, Scott W.
Purpose: Coagulopathy resulting from chronic liver disease (CLD) creates uncertainty regarding the risks and efficacy of pharmacologic venous thromboembolism (VTE) prophylaxis (ppx). We aim to describe patient characteristics associated with VTE ppx and the clinical impact of ppx in hospitalized patients with CLD. Methods: This retrospective study included patients with CLD, an international normalized ratio (INR) of ≥1.3, and hospital stay of ≥72 hours. Baseline characteristics, incidence of VTE, and major bleeding were compared between patients given ppx and those not given ppx. Results: Of 300 patients with CLD included, 157 (52%) received VTE ppx. Characteristics associated with VTE ppx were lower activated partial thromboplastin time, INR, bilirubin, and Model for End-Stage Liver Disease (MELD) score as well as a higher Padua Prediction Score, hemoglobin, platelet count, and antiplatelet use. VTE occurred in 12 (7.6%) ppx versus 4 (2.8%) non-ppx patients ( P = .07). Major bleeding occurred in 47 (30%) ppx versus 49 (34.3%) non-ppx patients ( P = .46). Ppx was not associated with VTE or bleeding outcomes by multivariate regression. Conclusion: The use of VTE ppx in hospitalized patients with CLD was not associated with a lower risk of VTE nor did it increase the risk of bleeding. Further studies examining the risks and benefits of VTE ppx in this population are needed.